Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jebo.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The earned income tax credit, mental health, and happiness

Abstract: This paper contributes to the small but growing literature evaluating the health effects of the Earned Income Tax Credit (EITC). In particular, we use data from the National Survey of Families and Households to study the impact of the 1990 federal EITC expansion on several outcomes related to mental health and subjective well-being. The identification strategy relies on a difference-indifferences framework to estimate intent-to-treat effects for the post-reform period. Our results suggest that the 1990 EITC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 68 publications
1
73
1
Order By: Relevance
“…Strully et al (2010) and Markowitz et al (2017) additionally show that state-level EITCs can improve birth outcomes. Four studies that have focused on outcomes related to health have shown that the EITC increases employer-sponsored health insurance coverage (Baughman 2005), reduces smoking of mothers (Averett and Wang 2013), and improves both child development (Hamad and Rehkopf 2016) and subjective well-being of mothers (Boyd-Swan et al 2016).…”
Section: Previous Literaturementioning
confidence: 99%
“…Strully et al (2010) and Markowitz et al (2017) additionally show that state-level EITCs can improve birth outcomes. Four studies that have focused on outcomes related to health have shown that the EITC increases employer-sponsored health insurance coverage (Baughman 2005), reduces smoking of mothers (Averett and Wang 2013), and improves both child development (Hamad and Rehkopf 2016) and subjective well-being of mothers (Boyd-Swan et al 2016).…”
Section: Previous Literaturementioning
confidence: 99%
“…In this paper, we contribute to the knowledge base about the effects of U.S. based EITC programs by focusing on the effects of states’ EITC on infant health outcomes and maternal health behaviors. A number of studies have examined the health effects of the federal EITC while ignoring state EITCs (Averett & Wang, 2013; Baker, 2008; Boyd-Swan et al, 2016; Evans & Garthwaite, 2014; Hamad & Rehkopf, 2015; Hoynes et al, 2015). These studies consistently find improvements in various measures of maternal and child health associated with the federal EITC.…”
Section: Introductionmentioning
confidence: 99%
“…Other work on the EITC has shown that the program reduces depression and increases happiness and self-esteem (Boyd-Swan, Herbst, Ifcher, & Zarghamee, 2016), and improves physical and mental health outcomes (Averett & Wang, 2013;Boyd-Swan et al, 2016;Evans & Garthwaite, 2014;Lenhart, 2019), birth outcomes (Hoynes, Miller, & Simon, 2015;Hamad & Rehkopf, 2016;Markowitz, Komro, Livingston, Lenhart, & Wagenaar, 2017), and health insurance coverage (Baughman, 2005;Baughman & Duchovny, 2016;Hoynes et al, 2015;Lenhart, 2019). It appears likely that expansions of the program affects the levels of financial security and stress for low-income families and that a combination of these factors can explain a potential association between EITC benefits and suicides.…”
mentioning
confidence: 99%